Effectiveness and safety of adjuvant software based on virtual reality for post-thoracoscopic surgery pain: study protocol for a randomized controlled trial - Xijia Feng; Wei Guo; Benyuan Jiang; Tong Li; Yi Lu; Song Xu; Wenzhao Zhong; Hecheng Li (Trials)
Abstract Background Postoperative pain can significantly impair functional recovery and diminish the quality of life in patients who have undergone thoracoscopic surgery. Virtual reality (VR), by leveraging cognitive-behavioral intervention techniques and redirecting attention from noxious stimuli, holds promise as a modality to alleviate postoperative pain. Despite this potential, current VR software for postoperative care predominantly emphasizes physical therapy and rehabilitation, often overlooking the integration of pain management strategies. The primary objective of our study is to evaluate the effectiveness and safety of an adjunctive VR-based software for pain control following thoracoscopic surgery. Methods This is a prospective, multicenter, open-label, randomized controlled trial involving 215 patients who have undergone thoracoscopic surgery. Participants will be randomly allocated to one of two parallel groups. The experimental group will receive postoperative adjuvant analgesic software in addition to standard postoperative pharmacological analgesia, while the control group will receive only standard postoperative pharmacological analgesia. Pain intensity will be assessed using the numerical rating scale (NRS) at pre-intervention and at 24 and 48 h post-surgery. The primary outcome measure will be the effectiveness of the VR-based adjuvant analgesic software, as assessed by the reduction in NRS scores after the second intervention at 48 h postoperatively compared to pre-intervention baseline at 24 h postoperatively, and the secondary outcome measure will assess its safety profile. Discussion Our study marks a pioneering effort to incorporate VR-based adjuvant software into the postoperative pain management regimen. We endeavor to explore an innovative approach to deliver evidence-based pain treatments. The findings of this trial aim to shed light on the potential benefits of VR as a complementary tool to traditional analgesic therapies in the context of postoperative pain management following thoracoscopic procedures. Trial registration Our protocol was retrospectively registered in the Chinese Clinical Trial Registry on August 2, 2024. The registration number was ChiCTR2400087741.